Plan de Marketing para la empresa Plásticos y Supermercado San José - Torres Rosales, Raquel Alejandra (2024)
The research employed interviews and surveys, with the former directed at the administrator of Plásticos y Supermercados San José and the latter at current customers in Ibarra. The collected data was analyzed using Google Forms. The main objective is to design a marketing plan for the company in Ibarra, analyzing its internal and external situation, defining objectives and strategies, and establishing a control system with relevant KPIs and metrics. The conclusion highlights the need to digitize the company's marketing strategies, as young customers prefer digital media. The results reveal a positive perception of the company for its prices and variety, but also point out the lack of digitization as an opportunity for improvement. Most of the respondents, belonging to the millennial generation, desire a greater presence on social media and an e-commerce platform. The justification lies in the need to adapt to current consumption trends, with the rise of digitization and the use of social networks for the purchase and consultation of products, to improve customer satisfaction and attract a new consumer base, thereby strengthening its position in the market.